URGENSI ANALISIS WACANA KRITIS DALAM BERITA ONLINE - Egi Sugianti; Asep Saepurokhman; E. Sulyati (Literat - Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The researcher considers the development of discourses in online news to be important and urgent. The diversity of online media leads to a variety of information, making it essential for readers to have the ability to select and analyze information from various sources. With the ease provided by the features of online media, there is an abundance of information that may not align with reality. Therefore, through critical discourse analysis, we can not only understand the content of the news but also uncover how the news text is presented, why the message is delivered in a particular way, and even delve deeper into exposing the misuse of power, domination, and injustice that are subtly exercised and produced through these news texts. Mass media and discourse are two elements that mutually support each other. Even the highest-quality critical discourse cannot stand alone; such discourse requires the mass media to encompass it. While the existence of discourse depends heavily on the surrounding mass media, mass media, in turn, depends on its audience or users. Therefore, an ideal mass media is not only judged by the content it publishes but also by the ease of access it provides to its users. With all the impacts it can generate, discourse is not merely a text with a specific writing purpose. Critical discourse is viewed as a multi-dimensional object of study that comprises several aspects: action, context, history, power, and ideology.